PEMANFAATAN LIMBAH CAIR TEMPE MENGGUNAKAN BAKTERI Pseudomonas sp DALAM PEMBUATAN PUPUK CAIR - Nur hayati (JURNAL TECHLINK, 2018)
This study aims to analyze the differences in the length of fermented tempeh wastes using Pseudomonas sp bacteria in the manufacture of liquid fertilizer, nutrient content (Nitrogen) contained in tempeh liquid waste fermentation using Pseudomonas sp bacteria in the manufacture of liquid fertilizer, the number of bacteria in tempe liquid waste fermentation by using Pseudomonas sp bacteria in making liquid fertilizer. Quantitative methods, types of experimental research and observations with the aim of knowing the effect of fermentation time on the liquid fertilizer produced. The fermentation time used is, 0, 7 14. days while the volume of bacteria is 200 ml. The mathematical model of the factorial design trial design with 2 replications used is as follows, Mattjik and Sumertajaya (2000), conducted at the ITI Microbiology Laboratory Technical Implementation Unit on Jl. Raya PUSPITEK Serpong-Tangerang Selatan, from the beginning of sampling until the end of the check, starts from May to June 2018. The object of this research is the liquid waste of tempe derived from the results of boiling tempeh. In this study, the pH, nitrogen and total bacteria were seen before and after adding bacteria by fermentation. The results showed: (a) tempe liquid waste can be used as raw material for the manufacture of high-quality liquid organic fertilizer in accordance with the quality standard provisions (POC) with the addition of Pseudomonas sp in the fermentation method, (b) the increase in N content in this study was 1.52%, which is from the level of 0.56% pure urine after fermentation of N content to 2.08%.